Comparative Proteomic Analysis Shows an Elevation of Mdh1 Associated with Hepatotoxicity Induced by Copper Nanoparticle in Rats - Shu-wei DONG; Zhao-hui GAO; Xiao-yun SHEN; Hui-wen XUE; Xia LI (Journal of Integrative Agriculture, 2014)
Copper nanoparticle is a new material widely used in biological medicine, animal husbandry and industrial areas, but its potential toxicity to human health and environment remains unclear. In order to study the hepatotoxic mechanisms of nanoparticles copper, two-dimensional gel electrophoresis (2-DE) and matrix-assisted laser desorption/ionization time of flight mass spectrometry (MALDI/TOF MS) of proteomics technology were used to isolate and identify the differentially expressed proteins from liver, which associated with hepatotoxicity induced by copper nanoparticle in rats. In this study, we have screened 15 kinds of proteins related with hepatotoxicity, of which spot8212 was identified as Malate dehydrogenase (Mdh1). The mRNA expression trend of Mdh1 was consistent with the result of 2-DE by RT-PCR validation. Bioinformatics analysis showed that Mdh1 was stable and no signal peptides, subcellular location was in endoplasmic reticulum; it contained many functional sites such as malate dehydrogenase activity signal sites 155LTRLDHNRAKSQI167; α helixes and random coils were the two main elements. Homologous analysis demonstrated high homologous of Mdh1 in rats with mouse and human, and the phylogenetic tree of Mdh1 was constructed. The result indicated that copper nanoparticle could regulate up the Mdh1 protein expression so as to compensate the energy deficit. Energy metabolic disturbance may be a pathway for copper nanoparticle particles to exert the hepatotoxic effects in rats.